Implementasi Model Pembelajaran Cerdas Berbahasa Indonesia Fonik (CBI FONIK) dalam Menstimulus Kemampuan Menyimak Anak Usia Dini - Novenda Alfian Nur Putri; Ida Yeni Rahmawati; Dian Kristiana (Universitas Pendidikan Mandalika, 2022)
This study aims to describe the implementation of the Indonesian Phonics Intelligent Learning Model (CBI FONIK) in Stimulating Early Childhood Listening Ability in Pelangi Alam Kindergarten, Ponorogo. This study used a qualitative descriptive method. Observation, interview, and documentation were used to collect the data. This study used observation to see the application of listening skills using the Indonesian Phonics Smart learning model (CBI FONIK). Interviews were addressed to the principal, teachers, and students in group A. The child's achievement card served as documentation. Data analysis in this study used the Miles and Huberman model. It was carried out using the stages of data reduction, data presentation, and verification/drawing conclusions. The results showed that the Smart Indonesian Phonics (CBI FONIK) learning model used the pre-phonic level with the single-story poster and song technique. Its application is not only done in the classroom but mainly in the school environment (nature). Most children can listen well and can say any words they hear.